TRAINING ON SOCIAL MEDIA UTILIZATION FOR COMMUNICATION POLITICS TO CONSTITUENTS IN THE ASPIRATION HOUSE OF MUHAMMAD NUR PURNAMASIDI, JEMBER REGENCY - Agung Purwanto (UPT Penerbitan Universitas Jember, 2022)
The rapid development of communication technology presents social media on smartphone or popularlyknown as hand phone (HP). In January 2022, Kominfo reported that there were 307.1 million cellularconnections and this is more than Indonesia's population of 277.7 million. It mean the constituents of theDPR RI are social media users. The Aspiration House of H. Muhammad Nur Purnamasidi asconstituent organizations that have not used social media for political comunication to their constituents.The purpose of training on the use of social media for political communication tasks is to be able to usesocial media as a means of accurate and valid information. Training method was online activities withProblem Base learning and Brainstorming techniques. The results of the activity showed thatadministrators of the House of Aspirations H. Muhammad Nur Purnamasidi increased insight andunderstanding of the benefits of social media as a means of political communication to theconstituents.They feel that the ability to use social media is mandatory for constituent organizationsmembers as a means of keeping an electronic track record that have done. This training can overcome thegap in human resources of the constituent organizations personnel with knowledge of social media,content building techniques, and network building.Keywords: social media, campaign team, political communication, constituents.